2020
DOI: 10.26803/ijlter.19.8.15
|View full text |Cite
|
Sign up to set email alerts
|

Application of Rasch Model to Develop a Questionnaire for Evaluating the Quality of Teaching for Students’ Creativity Development

Abstract: The purpose of this research is to develop a questionnaire for evaluating the quality of teaching for creativity development. We use three methods for creating the questionnaire, namely, interviews, literature review, and expert consultation. The Rasch model was applied to assess the psychometric properties of the questionnaire in the first phase with the participation of 112 students. The results of the study indicated that all items had a point-measure correlation coefficient ranging between 0.312 and 0.757,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The development of psychological measurement tools at school includes the Rasch model, as proved by a research conducted by Bui et al (2020), which showed that the development of teaching quality evaluation questionnaires for creativity development was able to fulfil the principles of psychology assessment instrument development. Veas et al (2016) proved that the Rasch measurement model can accurately estimate the validity of a construct, intelligence test and academic values, for the calculation of students with low achievement.…”
Section: Related Researchmentioning
confidence: 99%
“…The development of psychological measurement tools at school includes the Rasch model, as proved by a research conducted by Bui et al (2020), which showed that the development of teaching quality evaluation questionnaires for creativity development was able to fulfil the principles of psychology assessment instrument development. Veas et al (2016) proved that the Rasch measurement model can accurately estimate the validity of a construct, intelligence test and academic values, for the calculation of students with low achievement.…”
Section: Related Researchmentioning
confidence: 99%
“…Research by Eliaumra et al (2022) analysis of the quality of diagnostic instruments with the Rasch model to measure the creativity of prospective biology teachers provides good results. Finally, the use of item quality analysis using the Rasch model on biology concept creativity question instruments for biology teachers also provides valid and reliable results (Bui et al, 2020).…”
Section: Introductionmentioning
confidence: 99%